ASSESSMENT OF WETLAND DEGRADATION USING GEOSPATIAL TECHNIQUES IN LAKE BOYO, SOUTHERN ETHIOPIA - LETEBO, TESFAYE; DETAMO, KIBEMO; TESFAY, ALEM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Although wetlands occupy less than 6% of the earth’s land area, they contribute a lot for ecosystem services than their small area implies. This study aims to model the wetland degradation of Boyo Lake using Geospatial techniques. This study uses Landsat 7 ETM for the year 2000 and 2010 while Landsat 8 OLI used for 2020. The imageries were extracted and geometrically corrected using boundary polygon data using Spatial Analyst Tool in ArcGIS 10.8. Supervised classification was performed using the Maximum Likelihood Classifier. A comparison of land cover statistics assisted in identifying the trend and rate of change at wetland over time. In 2000, water and wetland covered an area of 2743.9 ha (53.3%) and 1680.3 ha (32.7%) of the area, respectively. The analysis shows that water and wetland coverage declined to 1922.9 ha (37.4%) and 1309.4 ha (25.4%) while farmland have increased to 1765.23 ha (34.3%) in 2010. Subsequently, area coverage by water and wetland further declined to 1579.1 (30.7%) and 627.94 (12.21 %) respectively, in 2020. The area under wetland is threatened dramatically with increasing encroachment of farmland over the years. Protecting wetlands from degradation needs the multi-stakeholders involvement and policy enforcement.